Improved Robust Stability Criteria of Uncertain Neutral Systems with Mixed Delays - Zixin Liu; Shu Lü; Shouming Zhong; Mao Ye (Abstract and Applied Analysis)
The problem of robust stability for a class of neutral control systems with mixed delays is investigated. Based on Lyapunov stable theory, by constructing a new Lyapunov-Krasovskii function, some new stable criteria are obtained. These criteria are formulated in the forms of linear matrix inequalities (LMIs). Compared with some previous publications, our results are less conservative. Simulation examples are presented to illustrate the improvement of the main results.